DAMPAK PENERAPAN FAKTOR GREEN ACCOUNTING TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR PESERTA PROPER YANG LISTING DI BURSA EFEK INDONESIA TAHUN 2017-2019 - Apriliani Widyowati; Esti Damayanti (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
The benefits of Green Accounting are trying to reduce the negative effects of economic activities and system on environmental. Given the importance of profitability and environmental preservation, an evaluation to the factors that affect profitability is essential. This study aims to analyze and examine the factors of Green Accounting on Profitability of PROPER Participating Manufacturing Companies listed on Indonesia Stock Exchange. This research used secondary data which obtained from annual reports and sustainability reports of Manufacturing Companies, PROPER Rating Reports and through several related sites and the data analysis method used is multiple linear regression analysis. Before conducting multiple linear regression analysis, the classic assumption test is done first using SPSS v.16 program.